Female Infanticides and Foeticides: A Cognizance or an Ignorance - Giri, Sasmita; Mundra, Ruchita; Gupta, Aditi; Chakraborty, Sayantani; Misra, Siddharth (International Journal of Psychosocial Rehabilitation, 2019)
The violence against women is a great concern in India. Even though technology is advancing at a great rate by which we are able to fight rare diseases, we are still not able to cure the problem of female foeticide and infanticide. People are misusing technology for the determination of the gender of the foetus. A change in law is needed and stricter actions needs to be taken against people committing such crime.Method: A survey through questionnaire was conducted using which Primary Data was collected. Responses from two hundred and three married females were collected and the analysis of this data was done using SPSS and Tableau.Results: The study depicts the major reasons behind female foeticide and infanticide being performed as people prefer having a male child over female. Also, the society feels that empowering and educating a woman will help in improving the situation.Conclusions: The study implies female foeticide and infanticide is a major problem in India. Ultrasonography was designed to keep a check on the mother’s health but, people have been using it illegally to determine the gender of the foetus. The paper will help women understand the negative effects of the act on them and the society as a whole. Also, the government should bring out new plans for betterment of women.